The secondary bile acids, ursodeoxycholic acid and lithocholic acid, protect against intestinal inflammation by inhibition of epithelial apoptosis - Lajczak‐McGinley, Natalia K.; Porru, Emanule; Fallon, Ciara M.; Smyth, Jessica; Curley, Caitriona; McCarron, Paul A.; Tambuwala, Murtaza M.; Roda, Aldo; Keely, Stephen J. (Physiological reports, 2020)
Increased epithelial permeability is a key feature of IBD pathogenesis and it has been proposed that agents which promote barrier function may be of therapeutic benefit. We have previously reported the secondary bile acid, ursodeoxycholic acid (UDCA), to be protective in a mouse model of colonic inflammation and that its bacterial metabolism is required for its beneficial effects. The current study aimed to compare the effects of UDCA, LCA, and a non‐metabolizable analog of UDCA, 6‐methyl‐UDCA (6‐MUDCA), on colonic barrier function and mucosal inflammation in a mouse model of colonic inflammation. Bile acids were administered daily to C57Bl6 mice by intraperitoneal injection. Colonic inflammation, induced by addition of DSS (2.5%) to the drinking water, was measured as disease activity index (DAI) and histological score. Epithelial permeability and apoptosis were assessed by measuring FITC‐dextran uptake and caspase‐3 cleavage, respectively. Cecal bile acids were measured by HPLC‐MS/MS. UDCA and LCA, but not 6‐MUDCA, were protective against DSS‐induced increases in epithelial permeability and colonic inflammation. Furthermore, UDCA and LCA inhibited colonic epithelial caspase‐3 cleavage both in DSS‐treated mice and in an in vitro model of cytokine‐induced epithelial injury. HPLC‐MS/MS analysis revealed UDCA administration to increase colonic LCA levels, whereas LCA administration did not alter UDCA levels. UDCA, and its primary metabolite, LCA, protect against intestinal inflammation in vivo, at least in part, by inhibition of epithelial apoptosis and promotion of barrier function. These data suggest that clinical trials of UDCA in IBD patients are warranted. Bacterial metabolism of UDCA to LCA protects against DSS‐induced colonic inflammation by preventing epithelial apoptosis and promoting barrier function. In conditions of IBD, increased production of proinflammatory cytokines and chemokines from the epithelium leads to recruitment of immune cells to the mucosa. Incoming immune cells produce additional cytokines and mediators that can promote epithelial apoptosis, leading to loss of barrier function. Administration of ursodeoxycholic acid (UDCA) leads to the generation of lithocholic acid (LCA) in the colon which, in turn, acts on the epithelium to inhibit cytokine‐induced apoptosis, thereby promoting barrier function and protecting against inflammation.